An Effective Finite Control Set-Model Predictive Control Method for Grid Integrated Solar PV - Iresha Poonahela (16876005) (2021)
The grid integration of a photovoltaic solar system operating with maximum power point tracking is being presented in this paper. The system uses a dc-dc converter for power tracking while employing finite control set model predictive control (FCS-MPC) to govern the dc-ac inverter. An effective control scheme that employs only FCS-MPC in the entirety of its control layer is proposed, where three control objectives; the regulation of the dc-link voltage, the injection of active power, and the injection of reactive power to the main grid have been achieved within a single cost function. The controller avoids translating dc-link voltage deviations to the active power reference and controls all variables directly in the cost function. The controller’s feasibility has been evaluated through experiments where experimental testing using OPAL-RT has been carried out to prove the concept. The results show that all three control objectives can be achieved efficiently using the proposed method, with minimal error in the controlled variables. Furthermore, the controller shows high robustness against parameter mismatch and grid inductance variations. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2021.3122325